Growth and leaf anatomy of rubber clones (Hevea brasiliensis Muell. Arg.) IRR 400 series toward drought stress. Issue 1 (1st June 2022) - Pasaribu, S A; Basyuni, M; Purba, E; Tistama, R
Abstract: The growth and leaf anatomy of plants in general time will changes when cultivated in drought area. An adaptation plant process that can be assessed from morphological characters. The research was conducted in a greenhouse and physiology laboratory at Sungei Putih Research Center, Indonesian Rubber Research Institute from June to September 2020. The study design is factorial randomized block design (RBD), the first factor is rubber clones (IRR 425, IRR 428, IRR 429, IRR 434, IRR 440, RRIC 100, BPM 24), the second factor is water content based on capasity field (CF) (30%, 60%, 90%) with repeated three times. The data is analyzed by MINITAB 6 software. If the analysis showed a significant difference, it would be continued by Tukey 5% test. The observed characters were plant height (cm), girth (mm), cuticle thickness (μm), stomata density and leaf relative water content (%). The results showed plant height and girth a decrease when the water content 30% CF, while cuticle thickness, stomata density and leaf relative moisture content appeared to be relatively same between among water content. IRR 434 clone is selected as clone with highest of plant height and stem diameter in drought stress.